Immersion Index in the Internet Environment: Questionary Standardization - Regush L.A.; Alekseeva E.V.; Veretina O.R.; Orlova A.V.; Pezhemskaya Ju.S. (Психолого-педагогические исследования)
The article presents the results of standardization of the questionary "Immersion Index in the Internet environment", intended for the adolescents aged 12 to 17 years. The questionary was based on theoretical analysis of the phenomenon of "immersion in the Internet environment", which allowed us to build its theoretical model and suggest that this phenomenon can be described through digital competence, digital consumption and emotional attitude to the digital environment. The standardization was carried out in two stages, with the participation of a total of 1142 teenagers from St. Petersburg. The first version of the questionnaire, tested for convergent validity, was adjusted in accordance with the results obtained. At the second stage, the questionnaire underwent the procedures of factorization, determination of reliability (Cronbach's Alpha coefficient), testing distribution normality, and age norms. The article presents a standardized version of the questionnaire "Immersion Index in the Internet environment" and instructions for processing the results.